PHONEMIC CHART MEDIA: TO IMPROVE THE STUDENTS’ PRONUNCIATION ON THE SECOND SEMESTER STKIP PGRI BANGKALAN (A CLASSROOM ACTION RESEARCH ) - Chairuddin Chairuddin (DIDAKTIKA, 2017)
The purpose of this article is to examine the pronunciation of the students in speakingclass through phonemic chart media. The findings from this report measure that most ofstudents had difficulties in the correct sound symbol, stress, rhythm, and intonation.More specifically, the results showed that the difficulties affected by many factors suchas lack of practicing, listening, imitating, and teaching learning process by the lecturercauses the students felt bored because the teaching learning process seemed to bemonotonous. These findings suggest that phonemic chart is one of solution in solvingthe problem of students’ pronunciation. The researcher believes this chart became agood media for students in enhancing their pronunciation ability and also to make theenjoyable situation in teaching learning process. In this research, the researcher used aclassroom action research in which the setting was conducted in STKIP PGRIBangkalan which involves one class of second semester students.